SPECTROSCOPICAL STUDY OF AN ETHER FRACTION ISOLATE FROM STEAM BARK OF “ JATI” (Tectona grandis, L) - Fredryk Mandey; Raimundus Chalik; Ismail Ibrahim (Indonesian Journal of Chemistry, 2009)
This research is aimed to primarily study the spectroscopy of ether fraction of from Jati wood (T. grandis, L). The stem bark of T.grandis, L was firstly extracted undergoes a reflux in methanol solvent. Further, the dried methanol crude extract was extracted with diethyl ether and moreover separated its chemical constituents by using of column chromatography using degraded mixtures of n-hexane - ethyl acetate from 9:1 to 7:3. After a final column chromatography from the E fraction, a white needles crystal with a melting point of 295 - 297.5 °C was resulted. This results was then confirmed undergoes a spectroscopic analysis including UV, FTIR, H-NMR, and Mass spectroscopy to get an acid of 3β-hydroxy-20(29)-lupen-28-oic or commonly known as betulinic acid.